Controllable Delay and Polarization Routing of Single Photons. Issue 2 (31st October 2019) - Maisch, Julian; Vural, Hüseyin; Jetter, Michael; Michler, Peter; Gerhardt, Ilja; Portalupi, Simone Luca
Abstract: Full control of single photons is important in quantum information and quantum networking. In particular, controlling the photon–atom interaction can be an appealing means to realize more complex quantum experiments. As a matter of example, the storage of photons into atomic media represents one key approach to memory‐assisted quantum communication and computing. Here it is shown that the propagation of single photons from a semiconductor quantum dot can be deliberately controlled by an atomic vapor under the application of an external magnetic field. The present results enable the use of an atomic vapor as a precise and reliable wavelength selective delay and allows for routing the single photons according to their polarization and the external magnetic field. With an overall delay of 25 ns, it is possible to fine‐tune the arrival time of the photons by more than 600 ps which matches the scale of the quantum dot's lifetime. The experimental data are fully reproduced by a theoretical model. Abstract : Full control of single photons is important in quantum information and quantum networking. Within the presented work, the delay of single photons from a semiconductor quantum dot via a hot atomic vapor is fine‐tuned by an applied external magnetic field. Simultaneously, it is possible to separate both circular polarization components in this configuration. Altogether, this study extends the tuning knobs for controlling the propagation of single photons.